Banco de semillas del suelo en el bosque montano en el Parque Universitario “Francisco Vivar Castro”, Loja, Ecuador - Mocha Gómez, Jonathan Javier (2020)
The seed bank is the set of viable seeds in and on the ground or associated with litter, which are capable of remaining dormant for long periods of time and germinate when environmental conditions are favorable, thus representing the regenerative potential of plant communities in a given environment. In this context, the composition and diversity of the vegetation of the arboreal and shrub stratum of the montane forest was studied; and its relationship with the composition of the soil seed bank in the “Francisco Vivar Castro” University Park; With the aim of knowing the potential of the natural regeneration of the woody species of the PUFVC, the study was carried out from November 2019 to August 2020. In the montane forest, six plots of 20 m x 20 m (400 m^2) were installed for the inventory of trees and shrubs, with five nested subplots of 2 m x 2 m (4 m^2); of which 30 samples of the organic layer and 30 samples of the mineral layer of the soil were extracted, said samples were placed in flex foam trays with transparent covers; maintaining the optimum temperature and humidity for the germination of the seeds. The samples were monitored for a period of 113 days with uninterrupted daily irrigation; The botanical identification of the species was carried out in the Herbarium "Reinaldo Espinosa" of the National University of Loja, the scientific names are reported according to APG IV. The floristic composition of the montane forest registered 238 individuals, belonging to 32 species, 26 genera and 24 botanical families, of which 59.37% are trees and 40.62% shrubs; While in the soil seed bank, 914 individuals were registered, belonging to 38 species, 27 genera and 23 botanical families, of which 0.5% are trees, 36% are shrubs, 60% are herbs. The floristic diversity according to the Shannon index in the montane forest is high with 4.27; like the soil seed bank with 3.99. The montane forest species with the highest importance value index (IVI) are: Palicourea amethystina, Viburnum triphyllum, Phenax laevigatus y Alnus acuminata; while for the soil seed bank they are: Cyperus rotundus, Tibouchina laxa, Phenax laevigatus, Calceolaria sp.1 y Viola arguta. The soil seed bank between the organic and mineral layers does not show significant statistical differences for the number of species and the number of individuals found with p = 0.06 and p = 0.1424 respectively, the variability for both parameters is greater 35%. The similarity between the floristic composition of the woody component of the montane forest and the seed bank of the soil of that forest is 14.6% with three shared species: Lepechinia mutica, Palicourea amethystina y Phenax laevigatus. Seed banks are the main source for the natural regeneration of woody species in the montane forest of the PUFVC; and why, they contain a reservoir of species for the successional process, which are apt to germinate at the moment of a disturbance. Keywords: Soil seed bank, organic layer, mineral layer, floristic composition, natural regeneration.